ENVIRONMENTAL HEALTH RISK ANALYSIS (SO2, NO2, CO and TSP) IN THE BONE BOLANGO AREA ROAD SEGMENT - Ayu Rofia Nurfadillah; Suparjan Petasule (Journal Health & Science : Gorontalo Journal Health and Science Community, 2022)
Air pollution occurs because of changes in normal conditions by including foreign substances in a certain time and for a long time. Air content is determined by the presence of substances such as carbon monoxide, dust/particles, sulfur dioxide (SO2), nitrogen oxides (NO2), hydrogen sulfide (H2S), and particulate matter (PM2.5, PM10, TSP). 70% of the cases of air pollution in urban areas are caused by motor vehicle emissions. Bone Bolango has a population that is increasing every year resulting in the development of an increasing number of transportation. This results in a decrease in air quality caused by several pollutants generated from exhaust fumes from motor vehicles. The purpose of this study was to analyze the risk of SO2, NO2, CO and TSP agents on the road section of the Bone Bolango area. This research is an observational study with an environmental quality risk analysis (ARKL) approach. Measurements of SO2, NO2, CO and TSP agents were carried out at four points, that is Jl. Huduido, Jl. Ratuwangi, Jl. Saptamarga, and Jl. Pasar Minggu which is a densely populated area. The measurement results show that the concentration of each risk agent is still below the safe limit of ambient air quality standards according to PP RI No. 22 Tahun 2021 concerning the Implementation of Environmental Protection and Management. The results of the risk analysis showed the level of risk of SO2, NO2, CO and TSP agents for the adult population, RQ1, meaning that it is not at risk for the adult population for the next 30 years. In addition to the level of risk for the population of children, only SO2 agents have an RQ1, meaning that it is have risk for the population of children for the next 30 years, while NO2, TSP and CO agents have an RQ value 1, meaning they are not at risk for children until the next 30 years. Conclusion Environmental Health Risks caused by So2, No2, Co and Tsp elements in the Bone Bolango Region Road are still below the safe limits of ambient air quality standards.Pencemaran udara terjadi karena adanya perubahan kondisi normal dengan dimasukkannya zat-zat asing dalam jumlah tertentu dan dalam waktu yang lama. Kadar pencemaran udara ditentukan oleh adanya zat-zat seperti karbon monoksida, debu/partikel, sulfur dioksida (SO2), nitrogen oksida (NO2), hidrogen sulfide (H2S) serta partikel (PM2,5, PM10, TSP). Sebagian besar kasus pencemaran udara diperkotaan 70% diantaranya disebabkan oleh emisi kendaraan bermotor. Bone bolango mempunyai jumlah penduduk yang semakin meningkat setiap tahunnya mengakibatkan perkembangan jumlah transportasi semakin meningkat. Hal ini berakibat pada penurunan kualitas udara yang diakibatkan oleh beberapa polutan yang dihasilkan dari pembuangan asap kendaraan bermotor. Tujuan penelitian ini yaitu menganalisis risiko agen SO2, NO2, CO dan TSP diruas jalan wilayah Bone Bolango. Penelitian ini termasuk penelitian observasional dengan pendekatan analisis risiko kualitas lingkungan (ARKL).  Pengukuran agen SO2, NO2, CO dan TSP dilakukan diempat titik yaitu ruas Jl. Huduido, Jl. Ratuwangi, Jl. Saptamarga, dan Jl. Pasar Minggu yang merupakan wilayah padat penduduk. Hasil pengukuran menunjukkan konsentrasi dari masing-masing agen risiko masih berada dibawah batas aman baku mutu udara ambien menurut PP RI no. 22 Tahun 2021, Penyelenggaraan Perlindungan dan Pengelolaan Lingkungan Hidup. Hasil analisis risiko menunjukkan tingkat risiko dari agen SO2, NO2, CO dan TSP untuk populasi dewasa yaitu RQ1, artinya tidak berisiko untuk populasi dewasa sampai 30 tahun mendatang. Selain itu tingkat risiko untuk populasi anak-anak, hanya agen SO2 yang memiliki RQ1, artinya berisiko untuk populasi anak-anak sampai 30 tahun mendatang, sedangkan agen NO2, TSP dan CO memiliki nilai RQ1, artinya tidak berisiko untuk anak-anak sampai 30 tahun mendatang. Kesimpulan Risiko Kesehatan Lingkungan yang disebabkan oleh unsur So2, No2, Co dan Tsp Di Ruas Jalan Wilayah Bone Bolango masih berada dibawah batas aman baku mutu udara ambien.